1989
DOI: 10.1002/j.0022-0337.1989.53.2.tb02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Construct and predictive validities of the Perceptual Ability Test

Abstract: The construct and predictive validities of the Perceptual Ability Test (PAT) were examined. The results indicate that the PAT is a multidimensional test of spatial abilities, with each of the PAT subtests exhibiting different predictive validity. Furthermore, a linear combination of the PAT subtest scores was found to be more predictive of first‐year dental school technique performance than the total PAT score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Manual dexterity is an important aspect of clinical dentistry, but despite many attempts to date, there are no standardized means of determining the manual dexterity potential of dental school candidates 1 5 . While Dental Admission Test (DAT) scores have been consistently shown to be valid predictors of academic performance in years one and two of dental school, 6 they are less useful as predictors of preclinical performance 7 . Of the individual DAT scores, the Perceptual Ability Test (PAT) score helps to explain the variance attributable to preclinical and clinical success 8 compared with the didactic or cognitive component alone 6 .…”
mentioning
confidence: 99%
“…Manual dexterity is an important aspect of clinical dentistry, but despite many attempts to date, there are no standardized means of determining the manual dexterity potential of dental school candidates 1 5 . While Dental Admission Test (DAT) scores have been consistently shown to be valid predictors of academic performance in years one and two of dental school, 6 they are less useful as predictors of preclinical performance 7 . Of the individual DAT scores, the Perceptual Ability Test (PAT) score helps to explain the variance attributable to preclinical and clinical success 8 compared with the didactic or cognitive component alone 6 .…”
mentioning
confidence: 99%
“…A selection instrument often used by dental schools is the Dental Admission Test. This includes a subtest concerning the ability to visualise patterns and relationships (8, 9), or what in psychometric terms is called spatial ability (10). A subtest of manual dexterity can also be included in the test (11).…”
mentioning
confidence: 99%
“…The DAT is also used by most Canadian universities, but the PAT is replaced by the Manual Dexterity Test (MDT), a soap carving pattern 13 , 14 . The reliability and predictive validity of DAT have been assessed in studies that found a low correlation coefficient with dental students’ clinical performance, 9 , 15 , 16 although more predictive results were found in the first and second years of dental school 9 …”
Section: Discussionmentioning
confidence: 99%